Cardiovascular computed tomography versus transoesophageal echocardiography after cryptogenic ischaemic stroke – a pilot study of 12 patients. Issue 1 (January 2020) - Resen, Mette Sørensen; Poulsen, Mai Bang; Overgaard, Karsten; Rasmussen, Rune Skovgaard; Soja, Anne Merete Boas; Nilsson, Brian; Kristensen, Mariana Obreja; Kruuse, Christina; Ulriksen, Peter Sommer
Objective: Transoesophageal echocardiography (TEE) is the gold standard for the detection of cardiac emboli sources in ischaemic stroke patients, but new computed tomography (CT) scanners are able to visualize the heart. This pilot study aimed to compare findings on TEE with combined cardiovascular scan and cerebral CT angiography in cryptogenic ischaemic stroke patients. Methods: This pilot study enrolled patients with cryptogenic ischaemic stroke who underwent a combined cardiovascular and cerebral CT angiography scan and a TEE examination, which were interpreted in a blinded manner. Results: Twelve patients with cryptogenic ischaemic stroke were included (mean age 56 years). Of these, 10 patients underwent both a combined cardiovascular and cerebral CT angiography and a TEE examination. All cardiovascular CT scans were readable at sinus rhythm. None of the simultaneous cerebral angiograms were compromised. Thrombi were not detected in any patients. Patent foramen ovale was visualized in five patients by TEE, while cardiovascular CT only identified three. Cardiovascular CT revealed in addition an X-ray negative pulmonary metastasis in one patient, aortic coarctation in another and significant coronary stenosis in four patients. Conclusion: The sensitivity for detecting patent foramen ovale was considerably lower for cardiovascular CT than for TEE, however the cardiovascular CT revealed several other very important clinical findings.